THE EMPOWERMENT MODEL OF CASH WAQF TO IMPROVE EDUCATION QUALITY IN ZAKAT INSTITUTIONS - Sri Herianingrum; Tika Widiastuti (IJIBE (International Journal of Islamic Business Ethics), 2016)
Islam has many solutions in addressing the issue of limitations in education. That is cash waqf. Cash waqf, is expected to narrow the gap between rich and poor society by means of transfering of wealth (the profits from managing cash waqf) from rich to poor. The purpose of this study is to analyze the cash waqf empowerment model in an effort to improve the quality of education. The method is done by in depth-interview with the boards (Leader and Manager program) of Yatim Mandiri, administrators of YKN (Independence Nusantara Foundation), and the staffs of Insan Cendekia Mandiri Boarding School. Limitation of this paper is to investigate the three institutions of zakat mentioned earlier. The results showed that waqfin the form of movable or immovable objects can be utilized and provide benefits to the society. The role of waqf, especially in improving the quality of education, is still limited to the purchase of land. The land is used for institution building of Insan Cendekia Mandiri Boarding School. There is a model of cashwaqf empowerment in the institution of zakat (Yatim Mandiri) that can be replicated in other institutions of zakat. The structure of this paper are: Section 1 describe the development of cash waqfin Indonesia; Section 2 is literature review about cash waqf; Section 3 explain the research model used in this paper; Section 4 is discussion; and the last Section 5 is the authors conclusion and authors recommendation to improve the empowerment of cash waqf.